2021
DOI: 10.1002/adem.202100087
|View full text |Cite
|
Sign up to set email alerts
|

Improving Tension/Compression Asymmetry of a Hot‐Extruded Mg–Zn–Y–Zr Alloy via Yttrium Addition

Abstract: In this study, effects of different yttrium (Y) contents ranging from 0 to 2.5 wt% on the microstructure and tension/compression asymmetry of as‐extruded Mg–5.5Zn–0.6Zr alloys are investigated. The influence of Y on improving the tension/compression yield strength is been studied. The results show that the volume fractions of the microscale I (Mg3YZn6) and W (Mg3Zn3Y2) phases remarkably increase with Y addition. Simultaneously, the nanoscale MgZn and Mg–Zn–Y phases uniformly precipitate during extrusion. Benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…It should be noted that a tension–compression asymmetry is found for a large variety of polymers 38–42 and other materials 43,44 . Therefore, this effect is not unique to the adhesive investigated in this work.…”
Section: Tension–compression Asymmetrymentioning
confidence: 81%
See 1 more Smart Citation
“…It should be noted that a tension–compression asymmetry is found for a large variety of polymers 38–42 and other materials 43,44 . Therefore, this effect is not unique to the adhesive investigated in this work.…”
Section: Tension–compression Asymmetrymentioning
confidence: 81%
“…It should be noted that a tension-compression asymmetry is found for a large variety of polymers [38][39][40][41][42] and other materials. 43,44 Therefore, this effect is not unique to the adhesive investigated in this work. In literature, however, implications of the asymmetry on the (equivalent) stress-based fatigue life prediction are hardly considered.…”
Section: Tension-compression Asymmetrymentioning
confidence: 95%
“…Table 1. It should be noted that a tension-compression asymmetry is found for a large variety of polymers [37][38][39][40][41] and other materials 42,43 . Therefore, this effect is not unique to the adhesive investigated in this work.…”
Section: Tension-compression Asymmetrymentioning
confidence: 99%
“…Next, Equation ( 15) and ( 16) are substituted into Equation ( 13) to obtain the stress increment dσ ij , as expressed in Equation (17).…”
Section: Stress-strain Relationshipmentioning
confidence: 99%
“…However, a phenomenon is often observed that some materials have different flow stresses between tension and compression, and it is defined as the strength differential effect or asymmetric yielding. [15][16][17] Concerning the constitutive modeling of the different metals and alloys, most attention has been devoted to the asymmetric yielding and hardening type. [18,19] Stoughton and Yoon [20] described the strength differential effect of sheet metal forming The TB9 titanium alloy is one of the most promising materials for engineering application due to high strength, high toughness, and corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%